ANALISIS IMPLEMENTASI PEMANFAATAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR IPAS KELAS IV DI SDN 21 LUBUK LINTAH - Tia septiana; Riri Marfilinda, Yeni Nurpatri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The utilization of the school environment as a learning resource is an effective strategy to enhance students' knowledge and understanding. This study aims to identify efforts and challenges in utilizing the school environment as a learning resource in the IPAS (Science and Social Sciences) subject for fourth-grade students at SDN 21 Lubuk Lintah.This research employs a qualitative method with a phenomenological approach, providing an in-depth description of the phenomena observed in the field. The research subjects include fourth-grade students and their homeroom teacher, while the research object focuses on the use of the school environment in IPAS learning. Data collection techniques involve observation, interviews, and documentation, with data validity tested through triangulation.The findings reveal that the school environment holds significant potential in enhancing students' cognitive abilities. This is evidenced by an increase in students' average scores from approximately 61 to 91 after the implementation of environment-based learning. Utilizing the environment as a learning resource also creates a more engaging and enjoyable learning atmosphere, while facilitating a better understanding of IPAS concepts.However, the study also identifies several obstacles, including limited supporting facilities and a lack of teacher creativity in designing environment-based learning activities. Therefore, systematic and sustainable strategies are needed to optimize the use of the school environment in order to improve student learning outcomes more evenly.